Raziskovanje govorjenega umetniškega jezika: Nina Žavbi - Krajnc Ivič, Mira (Stanje in perspektive uporabe govornih virov v raziskavah govora, 2024)
Researching Artistic Speech. The paper aims to show the development of research into artistic (stage) speech in Slovenia. It focuses on the contemporary research model that combines auditory-recognition and acoustic analysis. It defines the advantages of the method and presents a research strategy in interrelated steps: in the first step, the researcher compares the dramatic script with the transcript of the stage speech (that differs from the dramatic script due to dramaturgical cuts, the addition of texts, changes in the language genre, updated language, etc.); in the next step, the researcher analyses the realisation of the stage speech. In the context of the analysis, the stage speech is understood as only one of the staging factors. Interdisciplinary research contextualises the results and gives meaning to the study of the artistic phenomena of stage speech, which combines science and art.